Corrigendum [On Î²-Open Sets and Ideals in Topological Spaces, European Journal of Pure and Applied Mathematics, Vol. 12, No. 3, 2019, 893-905] (European Journal of Pure and Applied Mathematics, 2019)
Corrigendum